Phthalonitrile‐containing aromatic polyimide thin films with nano‐actuation properties. (8th October 2012) - Hamciuc, Corneliu; Carja, Ionela‐Daniela; Hamciuc, Elena; Vlad‐Bubulac, Tăchiţă; Ignat, Mircea
<x xml:space="preserve">Abstract</x> Polymer films of some polyimides containing pendant phthalonitrile groups were prepared by casting the corresponding poly(amic acid) solutions onto glass plates, followed by thermal imidization under controlled temperature conditions. The poly(amic acid)s were synthesized by polycondensation reaction of 4, 4′‐diamino‐4″‐(3, 4‐dicyanophenoxy)triphenylmethane, 1, or of different amounts of 1 and 4, 4′‐bis(4‐aminophenoxybiphenyl), with two aromatic dianhydrides, 4, 4′‐oxydiphthalic anhydride or benzophenone‐3, 3′, 4, 4′‐tetracarboxylic dianhydride. Most of the films were flexible and tough and exhibited high thermal stability, having the initial decomposition temperature above 400 °C. Dynamic mechanical analysis and dielectric spectroscopy revealed the influence of phthalonitrile group content on the relaxation processes of polyimides. The values of the dielectric constant at 10 kHz and 20 °C were in the range of 3.25–3.61. The films exhibited nano‐actuation in the range of 240–480 nm, depending on the phthalonitrile group content, when an electric voltage was applied on their surface. Copyright © 2012 John Wiley & Sons, Ltd.